Microwave assisted synthesis and X-ray structure of a novel anthracene-derived aminophosphonate. Enantioseparation of two α-aminophosphonates and genotoxicity in vivo. (3rd April 2017) - Kraicheva, I.; Tsacheva, I.; Nikolova, R.; Topashka-Ancheva, M.; Stoineva, I.; Shivachev, B.
GRAPHICAL ABSTRACT: ABSTRACT: A novel anthracene-derived α-aminophosphonate has been synthesized through a classical addition reaction of dimethyl phosphite to a Schiff base and via a microwave assisted Kabachnik–Fields reaction. The compound has been characterized by elemental analysis, TLC, IR, NMR, and fluorescent spectra. The X-ray analysis showed that the compound crystallizes in the orthorhombic space group Pbca (N° 61) with one molecule per asymmetric unit. The enantioseparation of two racemic aminophosphonates (5 and6 ) into enantiomers (5a, 5b and6a, 6b, respectively) has been performed. Data about genotoxicity and antiproliferative activity in vivo of the racemic compounds and their enantiomeric forms is also presented. The studied racemic α-aminophosphonates5 and6 and their enantiomers have weak genotoxic effect. Both pairs of enantiomers did not show a significant inhibition of cell dividing processes in the bone marrow cells compared to5 and6 . The hematopoietic function of the bone marrow will not be discontinued after exposure of the tested compounds.